Mediating Role of E- Learning Resources in Developing Entrepreneurial Inclinations Amongst Undergraduate Students At Universiti Utara Malaysia - Mohd Sufli Yusof, Dr.; Muhammad Salman Shabbir, Dr.; Muhammad Shukri Bin Bakar, Dr.; Dr. Mohd Noor Mohd Shariff, Prof.; Ramli, Azahari; Ahmad, Israr (International Journal of Engineering and Technology, 2018)
In this study the authors tried to identify mediating role of innovation and moderating role of size of enterprise in the relationship Making a living with lawful earnings is possible by working for others, becoming self-employed or employing others. This paper aims at providing insights into the role of structural support and the use of E-learning such as business simulations games in developing entrepreneurial intentions of university students. The underlying theories of experiential learning, constructivist learning theory and bloomâ€™s taxonomy are discussed in relation with the objectives of this study. The response of 252 university students from Malaysia was collected through self-administrative survey using simple random sampling technique. The results of PLS-SEM demonstrate a significant positive impact of E-learning resources and perceived structural support from Government in developing entrepreneurial inclinations of students at Universiti Utara Malaysia (UUM). The present study provides an overview and highlight the role assumed by the institutions of higher education through adoption of E-learning resources in order to nurture entrepreneurship among young generation. Additionally, keeping in view the role of higher education in socio-economic development, recommendations have also been proposed for universities and policy makings institutions to cope with the current challenges of higher education.Â The findings of this study have important implications of enhancing entrepreneurial capacity in Malaysia.